(untitled) (International Journal of Irrigation and Water Management, 2013)
Scarcity of water is the most severe constraint for development of agriculture in arid and semi-arid areas. Under this condition, irrigation management has to be improved while still achieving high yield. This study was conducted in North Gondar zone in 2010/2011 to investigate deficit irrigation scheduling on potato yield and yield components. Nine treatment combination: Irrigation frequency based on Cropwat model output, two modified irrigation frequency and two deficit irrigations of 25 and 50% were laid out with three replications in randomized complete block design (RCBD) in factorial combinations. It was found that irrigation scheduling significantly affected yield and some yield components. The highest marketable tuber yields was obtained from 0% deficit irrigation and frequency of F1-2 days (T9) which was 26.33 t ha-1 , whereas 25% deficit irrigation with F1-2 days frequency (T8) gave 25.68 t ha-1 . The lowest marketable yield was 3.4 t ha-1 from T4. The highest water use efficiency (WUE) were obtained from T7 and T8 which were 6.61 and 5.59 kg mm-1 , respectively. Therefore, applying 75% of full irrigation depth throughout the whole growing season with frequency based on Cropwat model scheduling -2 days resulted better potato yield and saved significant depth of water which improved WUE.